The Developmental Guidelines for the Professional Learning Community in School New Normal-Era under Khon Kaen Primary Educational Service Area Office 2 - Najaitruk, Warunya; Rooyuenyong, Wichian (Journal of Graduate MCU KhonKaen Campus, 2024)
This research is aimed to 1) study the needs of professional learning community in the new normal-era of schools under Khon Kaen Primary Educational Service Area Office 2 2) create developmental guidelines for a professional learning community in the school new normal-era under Khon Kaen Primary Educational Service Area Office 2. This is a mixed-method descriptive research. The sample group consisted of 60 school administrators and 264 teachers, totally 324 in number. The sample size was determined using the Taro Yamane formula at a sampling error level of .05, using the stratified random sampling method. The tool used is a 5-level estimation scale, finding the validity from the index of item objective congruence is between 0.66-1 for all items. The reliability of the entire questionnaire is at 0.91. The statistics used is semi-structured interview, with percentages, averages, and deviations, need index, and content analysis. The research found that 1. Necessity; they are arranged in the following order: 1) Professional Learning and Development, 2) Caring Community, 3) Shared Leadership, 4) Supportive Structure, 5) Collaborative Teamwork, and 6) Shared Vision 2. There are 6 developmental guidelines with 28 issues as follows: 1) Professional Learning and Development in the new normal-era has 7 issues. 2) Co-promoting Caring Community has 4 issues. 3) Positive Shared Leadership has 4 issues. 4) Supportive Structure has 4 issues, 5) Collaborative Teamwork has 5 issues, and 6) Shared Vision has 4 issues.